Minding Frankie - Binchy, Maeve (New York : Alfred A. Knopf, 2011)
Here is a tale of joy, heartbreak, and hope about a motherless girl collectively raised by a close-knit Dublin community.
Keywords: Recovering alcoholics -- Fiction; Child rearing -- Fiction; Fatherhood -- Fiction; Families -- Fiction; Interpersonal relations -- Fiction; Community life -- Ireland -- Fiction; City and town life -- Ireland -- Fiction; Domestic fiction